The Anopheles gambiae ATP‐binding cassette transporter family: phylogenetic analysis and tissue localization provide clues on function and role in insecticide resistance. Issue 1 (25th October 2017) - Pignatelli, P.; Ingham, V. A.; Balabanidou, V.; Vontas, J.; Lycett, G.; Ranson, H.
Abstract: The role of ATP‐binding cassette (ABC) transporters in conferring insecticide resistance has received much attention recently. Here we identify ABC transporters differentially expressed in insecticide‐resistant populations of the malaria vector, Anopheles gambiae . Although we found little evidence that the orthologues of the multidrug resistance proteins described in other species are associated with resistance in An. gambiae we did identify a subset of ABC proteins consistently differentially expressed in pyrethroid‐resistant populations from across Africa. We present information on the phylogenetic relationship, primary sites of expression and potential role of ABC transporters in mediating the mosquito's response to insecticides. Furthermore we demonstrate that a paralogous group of eight ABCG transporters, clustered on chromosome 3R, are highly enriched in the legs of An. gambiae mosquitoes, consistent with a proposed role for this ABC subfamily in transport of lipids to the outer surface of the cuticle. Finally, antibodies raised against one of the most highly expressed ABC transporters in adult females, ABCG7 (AGAP009850), localized this transporter to the pericardial cells. These data will help prioritize members of this gene family for further localization and functional validation studies to identify the in vivo function of these transporters in the mosquito and determine whether elevated expression of members of this family contribute to insecticide resistance.